Lipid peroxidation, proteins modifications, anti-oxidant enzymes activities and selenium deficiency in the plasma of hashitoxicosis patients. (October 2015) - Mseddi, Malek; Ben Mansour, Riadh; Mnif, Fatma; Gargouri, Bochra; Abid, Mohamed; Guermazi, Fadhel; Attia, Hamadi; Lassoued, Saloua
Objectives: The aim of this study was to explore the oxidative stress profile in hashitoxicosis (HTX) and to compare it with that of healthy subjects. Patients and methods: Spectrophotometric methods were used to evaluate the oxidative stress markers. The selenium level was investigated by atomic absorption. Results: High levels of thiobarbituric acid reactive species (TBARS) and conjugated dienes were found in HTX patients ( p = 0.034 and p = 0.043, respectively) compared with healthy controls. For antioxidant enzymes, superoxide dismutase (SOD) and catalase activities increased, whereas that of glutathione peroxidase (GPx) decreased ( p = 0.000, p = 0.014, p = 0.000, respectively) compared with controls. A reduction in the level of selenium ( p = 0.029) and thiol groups ( p = 0.008) were shown in patients; however, levels of carbonyl group and malondialdehyde (MDA) protein adducts decreased ( p = 0.000) compared with controls. Positive correlation was shown between levels of free thyroxine (FT4) and TBARS ( r = 0.711, p = 0.048) and between FT4 level and SOD activity ( r = 0.713, p = 0.047). Conversely, GPx activity presented a negative correlation with FT4 and free triiodothyronine (FT3) levels ( r = –0.934, p = 0.001; r = –0.993, p = 0.000, respectively). In addition, GPx activity showed positive correlation with selenium level ( r = 0.981, p = 0.019) and the FT3 level correlated negatively with the level of thiol groups ( r = –0.892, p = 0.017). Conclusions: This study shows the presence of an oxidative stress and selenium deficiency in HTX patients and suggests that the hyperthyroid state is strongly implicated in the establishment of this disturbed oxidative profile.